PENDIDIKAN KEWIRAUSAHAAN GUNA MEMPERSIAPKAN MAHASISWA DALAM MENGHADAPI PERSAINGAN MASYARAKAT EKONOMI ASEAN (MEA) - Erlina Zahar (Universitas Batanghari Jambi, 2018)
This paper is aimed at revealing (1) The role of entrepreneurship course in ASEAN Economic Community (AEC), and (2) The characteristics of entrepreneur in ASEAN Economic Community (AEC). This paper is made by relevance of library. The data are collected by documentation technique. The result of this paper show that (1) Entrepreneurship course is a really important course in university to create university graduate who have hard skill and soft skill as an entrepreneur. Moreover, they are able to face the competition in ASEAN Economic Community (AEC), and (2) An entrepreneur in ASEAN Economic Community (AEC) must have characteristics such as, goal-oriented, risk taking, confident, creative and innovative, be responsible, enthusiastic, and hardworking. Keywords: Entrepreneurship Course, ASEAN Economic Community